Discrete-time current regulator for AC machine drives - Yuan, Xin (2022)
In a practical alternating current (AC) machine drive system, a direct discrete-time current regulator model based on a zero order hold (ZOH) equivalent discrete-time machine model should be the first choice to be established compared with the discrete-time current regulator model based on continuous-time machine model when designing a digital current regulator. However, it is complicated to establish a direct discrete-time current regulator for asymmetric machine1 model due to the involvement of matrix exponential related to unequal machine inductance parameters. In order to overcome this issue, a simple direct discrete-time current regulator based on flux model is proposed, where a novel AC machine model is developed by employing a new feed-forward voltage compensation. In addition, a direct discrete-time flux observer with low parameter sensitivity is proposed to compensate the inherent one-step delay in practical systems. Simulation results and theoretical analysis have shown that the proposed discrete-time current regulator and flux observer have good parameter robustness and stability. Also, the experimental verification is performed on a AC machine drive test rig.